The prevalence and clinical aspects of Barrett's esophagus in the population of Eastern Siberia - N N Butorin (Терапевтический архив, 2013)
AIM: To study the prevalence and clinical aspects of Barrett's esophagus (BE) in natives and newcomers in East Siberia/MATERIAL AND METHODS: Clinical examinations and esophagogastroduodenoscopy were performed in 12975 Caucasoids and 1489 Khakases in Abakan (Khakasia), 1861 Caucasoids and 5829 Tuvinians in Kyzyl (Republic of Tuva), and 1177 Caucasoids in Dudinka (Taimyr). The diagnosis of BE was verified by morphological study/RESULTS: Among the Caucasoids, the total prevalence of BE was 1.6% (2.4% in men and 0.8% in women; odds ratio (OR) was 3.21 with 95% CI 2.40-4.29; p